(3GdJegjO aj Yde GdJLhjOs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , J (B833 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdbQBf GdYXje eaJGM BdGFg , hHYO aEf Chdi GdYdhe PcQkG hacQkG hCTQagG efRdI hbOQkG hCYXegG PNQkG haNQkG , cdGe ef Ndb ef GdeGA HTQkG s
(3BNQgG (B:s
(3aEPG YQagG hhVYgG ehGVYgG , abO QJd GdbQBf , hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HChdgG Jedc SfI (B1193 (3g`s
(3HOGNdgG fbU YfO GdhQbI (B18 (3, (B21 s
(3cJHJ HYV GdcdeGJ HGdMeQI s
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs